(untitled) (Tamaddun, 2025)
This study investigates the quality and effectiveness of Arabic language teaching materials used in Islamic schools, focusing on curriculum alignment, pedagogical design, and learner engagement. Employing document analysis supported by teacher and student feedback, the research examines textbooks, modules, and supplementary resources from multiple madrasah aliyah. Drawing on theories of instructional design (Gagné, 1985) and communicative language teaching (Brown, 2007), a set of evaluative criteria was established to assess coherence, meaningfulness, adaptability, and integration of Islamic content. Findings indicate that while certain materials demonstrate structured progression and robust alignment with curricular objectives particularly in integrating religious references in a pedagogically meaningful manner others exhibit significant shortcomings. These include incomplete coverage of core linguistic competencies, overreliance on rote memorization, and limited capacity to accommodate diverse student proficiency levels. Data triangulation confirms that materials with clearly defined objectives and interactive tasks foster higher learner motivation and deeper language acquisition, as evidenced by positive teacher and student feedback. The results underscore an urgent need for more consistent quality standards and systematic review processes in the development and selection of Arabic teaching materials. They further highlight the potential of culturally contextualized, learner-centered resources to enhance both linguistic proficiency and religious understanding. The study’s findings have implications for policy-makers, curriculum designers, and educators, suggesting that targeted improvements in material design and teacher training can lead to more effective Arabic instruction in Islamic educational contexts.